2017
DOI: 10.1371/journal.pone.0187671
|View full text |Cite
|
Sign up to set email alerts
|

Agomelatine, venlafaxine, and running exercise effectively prevent anxiety- and depression-like behaviors and memory impairment in restraint stressed rats

Abstract: Several severe stressful situations, e.g., natural disaster, infectious disease out break, and mass casualty, are known to cause anxiety, depression and cognitive impairment, and preventive intervention for these stress complications is worth exploring. We have previously reported that the serotonin-norepinephrine-dopamine reuptake inhibitor, venlafaxine, as well as voluntary wheel running are effective in the treatment of anxiety- and depression-like behaviors in stressed rats. But whether they are able to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 54 publications
4
32
0
1
Order By: Relevance
“…Upon exposure to repeated RST, all mice exhibited the expected depressive-like behaviors with at least 14 days of exposure to RST, as reflected by prolonged immobility, decreased locomotion, and thigmotactic responses (the time spent in the periphery) in the TST, FST, and OFT, all of which are widely used for assessing anxiety- and depressive-like behaviors in research using rodents [ 18 – 20 ]. These results are consistent with previous studies [ 17 , 23 , 24 ] which demonstrated adaptive behavioral changes, suggesting that C57BL/6 N mice derived from different sources develop a similar degree of depressive-like behaviors upon exposure to repeated RST.…”
Section: Discussionsupporting
confidence: 93%
“…Upon exposure to repeated RST, all mice exhibited the expected depressive-like behaviors with at least 14 days of exposure to RST, as reflected by prolonged immobility, decreased locomotion, and thigmotactic responses (the time spent in the periphery) in the TST, FST, and OFT, all of which are widely used for assessing anxiety- and depressive-like behaviors in research using rodents [ 18 – 20 ]. These results are consistent with previous studies [ 17 , 23 , 24 ] which demonstrated adaptive behavioral changes, suggesting that C57BL/6 N mice derived from different sources develop a similar degree of depressive-like behaviors upon exposure to repeated RST.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to selective serotonin reuptake inhibitors, physical activity can also lead to raise in tryptophan and is a precursor of serotonin, resulting in an increased serotonin in the brain. Thus, it can avoid disruption of serotoninergic signaling and may have antidepression‐like effect on NPs . Both norepinephrine and serotonin stimulation are 2 important factors in enhanced brain‐derived neurotrophic factor (BDNF) transcription following physical exercise .…”
Section: Potential Mechanisms Of Physical Activity On Npsmentioning
confidence: 99%
“…Thus, it can avoid disruption of serotoninergic signaling and may have antidepression-like effect on NPs. 60,61 Both norepinephrine and serotonin stimulation are 2 important factors in enhanced brainderived neurotrophic factor (BDNF) transcription following physical exercise. 57 It is well known that BDNF is a fundamental mediator to regulate neuronal survival, synaptic plasticitya, and neurogenesis in the brain, in particular in the hippocampus, which is the cerebral area mainly involved on memory and behavior.…”
Section: Key Pointsmentioning
confidence: 99%
“…Studies have shown that exercise improves cognitive deficits 48 , 49 and enhances levels of BDNF in the brain 50 , 51 and reduces the risk of neuropsychiatric diseases. 52 , 53 BDNF plays an important role in mediating the effects of exercise on brain functions. 50 Environmental enrichment (EE) is another beneficial intervention for improving anxiety and depression-like behaviors.…”
Section: Introductionmentioning
confidence: 99%